Construction of Knowledge about Fractional Number A Construção do Conhecimento sobre Número Fracionário - Nilza Eigenheer Bertoni (Universidade Estadual Paulista, 2008)
Studies, experimentation, and reflections over the course of twenty years have led our investigations in the direction of students' construction of the concepts of fraction and fractional number. Distinct trends can be identified in our investigations over the years, each resulting from and reviewed following observations of students' thinking and reactions as well as the depth and reach of the knowledge constructed. In the first of these phases, we used manipulative material; in the second, reflexive abstractions regarding divided geometric figures; in the third, objects that showed themselves divided in the real world, which led us to situations involving these objects and their associated fractional numbers. This revealed to us an interface with the ideas of Vergnaud regarding the formation of concepts, presented in the Theory of Conceptual Fields. We began to investigate and experiment with the development of a proposal for learning fractional numbers according to the elements of this conception, which includes initial situations, schemes of the students in action, and representations of the concept. In this context, we present the trajectory of our work, a re-elaboration of the proposal in the final phase, and our findings. The proposal we developed centers on the learning of fractions in the construction of a number, making explicit its aim and what it quantifies, as well as its relations with natural numbers. Key-words: Fraction as number. Vergnaud - Formation of Concepts. Counting, Division, Measures prioritized in relation to Divided Geometric Figures. Estudos, experimentações e reflexões ao longo de vinte anos conduziram nossas investigações na direção da construção dos conceitos de fração e de número fracionário pelos alunos. Nesses anos, distintas tendências ocorreram em nossas investigações, cada uma decorrente de e revista após observações do pensar e agir do aluno, bem como da profundidade e alcance do conhecimento construído. Na primeira dessas fases, usávamos material manipulativo; na segunda, abstrações reflexivas sobre figuras geométricas divididas; na terceira, objetos que se apresentavam divididos no mundo real, o que nos levou a situações que envolvessem esses objetos e aos números fracionários associados. Isso nos revelava uma interface com idéias de Vergnaud sobre a formação de conceitos, apresentada na Teoria dos Campos Conceituais. Passamos a investigar e experimentar o desenvolvimento de uma proposta para a aprendizagem dos números fracionários seguindo os elementos dessa concepção, que inclui situações iniciais, esquemas dos estudantes na ação e representações do conceito. Nesse texto, apresentamos a trajetória de nosso trabalho, a re-elaboração da proposta na última fase e resultados obtidos. A proposta que desenvolvemos centra a aprendizagem das frações na construção de um número, explicitando a que vem esse número e o que ele quantifica, bem como suas relações com os números naturais. Palavras-chave: Fração como Número. Vergnaud - Formação de Conceitos. Contagem, Divisão, Medida priorizadas em relação a Figuras Geométricas Divididas.